2015
DOI: 10.1016/j.rbo.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Concordância intra e interobservadores do sistema de classificação AO para fraturas dos ossos longos na população pediátrica

Abstract: Como citar este artigo: Utino AY, et al. Concordância intra e interobservadores do sistema de classificação AO para fraturas dos ossos longos na população pediátrica. Rev Bras Ortop. 2015. http://dx.RBO-936; No. of Pages 8 r e v b r a s o r t o p . 2 0 1 5;x x x(x x):xxx-xxx w w w . r b o . o r g . b r Artigo original Concordância intra e interobservadores do sistema de classificação AO para fraturas dos ossos longos na população pediátrica ଝ informações sobre o artigo Histórico do artigo: Recebido em 8 de ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Audigé et al 13 evaluated 44 reproducibility studies on orthopedic classifications with the use of imaging criteria and found little uniformity in the methodology, which hinders the comparison of reproducibility. Belloti et al 6 assessed the reproducibility of distal radius fracture classifications, while Utino et al 14 studied the agreement in the AO classification for long bones in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Audigé et al 13 evaluated 44 reproducibility studies on orthopedic classifications with the use of imaging criteria and found little uniformity in the methodology, which hinders the comparison of reproducibility. Belloti et al 6 assessed the reproducibility of distal radius fracture classifications, while Utino et al 14 studied the agreement in the AO classification for long bones in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…The number of radiographs and observers in this study is therefore within the norms found in the literature. 6,13,14,[16][17][18][19][20][21][22][23][24] The higher the number of categories in a classification, the worse the agreement. 6,18 Albertoni's classification, with seven possible options, would tend to have a worse agreement when compared with other classifications.…”
Section: Discussionmentioning
confidence: 99%